A groundwater well database for Brazil (GWDBrazil) - Uchôa, José Gescilam S. M.; Oliveira, Paulo Tarso S.; Ballarin, André S.; Gastmans, Didier [UNESP]; Anache, Jamil A. A.; Scanlon, Bridget R.; Camacho, Clyvihk R.; Freddo Filho, Valmor J.; Wendland, Edson C. (Springer Nature, 2025)
Sufficient spatiotemporal in-situ groundwater-level measurements are essential for sustainable water management. Despite their importance, lack of harmonized, quality-controlled datasets has hindered large-scale groundwater studies in Brazil. In collaboration with the Geological Survey of Brazil, we present the Groundwater Well Database for Brazil (GWDBrazil), which consolidates and standardizes information from over 351,000 wells, with records dating from 1900 to 2024, including about 450 wells with continuous daily monitoring from 2010 to 2024. Cross-verification steps were applied to ensure data accuracy. GWDBrazil is available in both tabular format and vector points, comprising information such as location, well depth, and well purpose. The dataset also provides data to support integrated surface water and groundwater management, such the distance from each well to the nearest river and aquifer information. This dataset is intended to serve as a valuable resource for researchers, decision-makers, and stakeholders, providing essential information to support comprehensive water management strategies in Brazil.